Effect of Dietary Supplementation of Turmeric (Curcuma Longa) on Health Status of Young Pigs During Pre and Post Weaning Periods - Stevenson, Joseph Lalruatkima; Kalita, Girin; Goswami, Ranjana; Das, Hemen; Sarma, Kalyan; Ali, Mohammad Ayub; Das, Biren Kumar; Samanta, Arup Kumar; Mayengbam, Prava; Tolenkhomba, T. C.; et al. (International Journal of Bio-resource and Stress Management, 2023)
The present research programme was conducted to study the effect of turmeric (Curcuma longa) powder supplementation on the growth performance and health status of Large White Yorkshire young pigs. A total number of 128 (12 litters) young pigs weaned at 28 days old were taken for the study period of 56 days. The young pigs in their respective litters were randomly divided into three groups viz., Control (C) fed basal diet, Treatment-1 (T1) fed basal diet+0.5% turmeric powder and Treatment-2 (T2) fed basal diet+1% turmeric powder in such a way that there were 4 replicates in each group with 1 litter as one replicate. Parameters recorded were general appearance, occurrence rate of diarrhea and faecal consistency. Statistical analysis revealed significant (p<0.05) differences in general appearance score during the post-weaning periods. Statistical analysis also revealed significant (p<0.05) differences in occurrence rate of diarrhoea (%) on 5th week under three different groups and significant (p<0.05) differences between the different groups during the post weaning (5th to 8th week) period, highly significant (p<0.01) differences in faecal consistency score between the groups during post weaning (5th to 8th week) and overall (1st to 8th week) periods. It may be concluded that dietary inclusion of dry turmeric powder at 1.0% level in pre and post weaning diets is beneficial - for growth performance of LWY young pigs especially during post weaning period.